Harder-Narasimhan filtrations of persistence modules - Fersztand, M; Jacquard, E; Nanda, V; Tillmann, U (Wiley, 2024)
The Harder–Narasimhan (HN) type of a quiver representation is a discrete invariant parameterised by a real-valued function (called a central charge) defined on the vertices of the quiver. In this paper, we investigate the strength and limitations of HN types for several families of quiver representations which arise in the study of persistence modules. We introduce the skyscraper invariant, which amalgamates the HN types along central charges supported at single vertices, and generalise the rank invariant from multiparameter persistence modules to arbitrary quiver representations. Our four main results are as follows: (1) We show that the skyscraper invariant is strictly finer than the rank invariant and incomparable to the generalised rank invariant; (2) we characterise the set of complete central charges for zigzag (and hence, ordinary) persistence modules; (3) we extend the preceding characterisation to rectangle-decomposable multiparameter persistence modules of arbitrary dimension; and finally, (4) we show that although no single central charge is complete for interval-decomposable ladder persistence modules, a finite set of central charges is complete.